PEDAGOGICAL TECHNOLOGY OF HUMANISM AND SELF-GIVEN LOVE OF PERSONALITY CHILDREN ARE AN IMPORTANT CORE OF HUMAN VALUES (Pedagogy of Higher and Secondary Education, 2007)
The article is devoted to the pedagogical technology of humanism and selfless love to the child's personality as an important nucleus of the human values.